GE_GERICHTE P/7463/2020 vom 7. März 2025 - GE Cour de justice (2025)
POSITION DE GARANT;HOMICIDE PAR NÉGLIGENCE;OMISSION DE PRÊTER SECOURS;RECOURS JOINT | CP.128; CP.11; CP.117; CPP.401; LNI.22; LNI.23; LNI.24